Collaborative writing: The effects of metacognitive prompting and structured peer interaction - Yarrow, Fiona; Topping, Keith J. (British Journal of Educational Psychology, 2001)
Background. The structured system for peer assisted learning in writing named Paired Writing (Topping, 1995) incorporates both metacognitive prompting and scaffolding for the interactive process. Aim....